CD16+ Monocytes and Skewed Macrophage Polarization toward M2 Type Hallmark Heart Transplant Acute Cellular Rejection - van den Bosch, Thierry P. P.; Caliskan, Kadir; Kraaij, Marina D.; Constantinescu, Alina A.; Manintveld, Olivier C.; Leenen, Pieter J. M.; von der Thüsen, Jan H.; Clahsen-van Groningen, Marian C.; Baan, Carla C.; Rowshani, Ajda T. (Frontiers in Immunology, 2017)
Background: During acute heart transplant rejection, infiltration of lymphocytes and monocytes is followed by endothelial injury and eventually myocardial fibrosis. To date, no information is available on monocyte-macrophage related cellular shifts and their polarization status during rejection. Here, we aimed to define and correlate monocyte-macrophage endomyocardial tissue profiles obtained at rejection and time-points prior to rejection, with corresponding serial blood samples in 25 heart transplant recipients experiencing acute cellular rejection. Additionally, 33 healthy individuals served as control. Material and Methods: Using histology, immunohistochemistry, confocal laser scan microscopy and digital imaging expression of CD14, CD16, CD56, CD68, CD80 and CD163 was explored to define monocyte and macrophage tissue profiles during rejection. Fibrosis was investigated using Sirius Red stainings of rejection, non-rejection and one-year biopsies. Expression of co-stimulatory and migration-related molecules on circulating monocytes, and production potential for pro- and anti-inflammatory cytokines were studied using flowcytometry. Results: At tissue level, striking CD16+ monocyte infiltration was observed during rejection (p<0.001). Significantly more CD68+CD163+ M2 macrophages were documented during rejection compared to barely present CD68+CD80+ M1 macrophages. Rejection was associated with severe fibrosis in 1-year biopsies (p<0.001). Irrespective of rejection status, decreased frequencies of circulating CD16+ monocytes were found in patients compared to healthy individuals. Rejection was reflected by significantly increased CD54 and HLA-DR expression on CD16+ monocytes with retained cytokine production potential. Conclusions: CD16+ monocytes and M2- macrophages hallmark the correlates of heart transplant acute cellular rejection on tissue level, and seem to be associated with fibrosis on the long-term.